Comparison of the sensory properties of ultra-high temperature (UHT) milk from different countries and preference mapping of UHT milk between U.S. and Thai consumers - Oupadissakoon, Gaewalin (Kansas State University, 2007)
Ultra-high temperature (UHT) milk is marketed as a convenience product in the United States (U.S.) and as the most common form of milk in many other parts of the world. Two studies were conducted to get a better understanding of sensory properties and consumer acceptability in UHT milk. First study compared the differences in flavor and texture of commercial UHT milk from different countries (France, Italy, Japan, Korea, Peru, Thailand, and the U.S.). A total of 37 UHT and sterilized milk samples including whole, 2% reduced-fat, and low-fat milk were evaluated. Five highly trained panelists used flavor and texture profiling to describe the sensory properties of each milk sample. Higher levels of processed, chalky, brown, and cooked flavor notes generally corresponded to lower levels of fresh dairy flavor characteristics. In general, samples did not vary consistently within a country. Interestingly, fat content did not correlate with dairy fat flavor or with viscosity. This research suggests that companies' manufacturing processes may have more impact than country or fat content in determining quality of UHT milk. Second study compared UHT milk acceptability by U.S. milk consumers unused to UHT milk and Thai consumers who typically drank UHT milk. Preference mapping technique was used to study sensory characteristics of UHT milk that drive overall liking from each of those consumer groups. Consumer studies were conducted in Bangkok, Thailand and in Manhattan, Kansas with one hundred consumers participating in each location. Both groups of consumers evaluated five commercial UHT whole milks that represented a range of UHT milk properties. U.S. consumers thought that the UHT milks had more off-flavor and liked them overall less than did Thai consumers. Results from the external preference map showed that both groups of consumers liked UHT milk with more dairy characteristics and higher fat feel. However, there was a separate group of Thai consumers who liked UHT milk with processed, cooked, and brown flavors. Lack of freshness, butyric acid, and sour aromatics were undesirable sensory attributes in UHT milk, regardless of consumer population. Off-flavors in the UHT milks in this study may be described with those attributes.
Keywords: milk; UHT; sensory; flavor; texture; acceptability; Agriculture, Food Science and Technology (0359)